ПРИМЕНЕНИЕ ТРИГОНОМЕТРИЧЕСКИХ ФУНКЦИЙ ПРИ ДИАГНОСТИКЕ СЕРДЕЧНЫХ ЗАБОЛЕВАНИЙ. (Multidisciplinary Journal of Science and Technology, 2026)
This paper examines the application of trigonometric functions in the diagnosis of cardiovascular diseases. Particular attention is paid to the analysis of the electrocardiogram (ECG) as a periodic signal that can be described using sinusoidal functions. Trigonometric methods have been shown to detect arrhythmias, analyze heart rhythm, and construct mathematical models of cardiac activity. This study demonstrates the importance of mathematical methods in modern medicine and their role in improving diagnostic accuracy.